The globalized governance of finance / David Zaring. - Zaring, David (Cambridge University Press, 2020)
Big banks are capable of wreaking havoc on the global economy, and governments have often felt powerless to stop them. Regulators have responded by developing coordinated programs to handle banks, insurers, broker dealers, shadow banks and other businesses that can blow up in a crisis. This program began informally and undemocratically, and has developed into something much more organized, formalized and predictable, even though it has never been legally enforceable. David Zaring examines the realities of the current international financial system and concludes that in fact this is a well-ordered and functioning regulatory environment: the international financial system enjoys a substantial degree of compliance, and operates predictably and harmoniously. As a result, perhaps this could serve as a paradigm for future global governance. Zaring explores three aspects of international financial regulation that can inform global governance: harmonization through rules, cooperation on enforcement and agreement on fundamental principles.